SISTEM RESELLER DALAM PRAKTIK JUAL BELI ONLINE SHOP - Ria Rosita; Budi Sufyanto Budi (Al-Hukmi : Jurnal Hukum Ekonomi Syariah dan Keluarga Islam, 2024)
This thesis discusses the Reseller system in Online Buying and Selling Practices from a Sharia Economic Law Perspective (Case Study of an Online Shop Fhie Store in Seletreng Kapongan Village, Situbondo). This researcher aims: To find out the mechanism of the 0nline reseller buying and selling system at the Fhie Store; To find out what the reseller system is from a sharia economic law perspective. In this study, researchers used descriptive qualitative. The research location at the Fhie Store online shop is located on Jalan PP. Nurul Iman Setonggak Seletreng Kapongan Situbondo. The research instruments used were cellphones, notebooks, interview guides. The data collection technique in this research is qualitative analysis. From the results of this research it can be seen that buying and selling using the reseller system in the Fhie Store online shop is a transaction that explains the properties of the objects or goods being bought and sold, all of this is done by order and in these transactions the reseller and consumer do not meet directly, and also the goods There are no ones for sale because they can only be shown in the form of photos with the specifications and prices stated in the photos. If viewed from the perspective of Sharia Economic Law, the reseller system in the Fhie Store online shop still needs to emphasize the principle of responsibility. Meanwhile, the principles of honesty and fairness are sufficiently applied in buying and selling transactions. The reseller system implemented in the Fhie Store online shop for resellers should broaden their knowledge of Sharia Economic Law. Meanwhile, consumers should be more responsible for the goods they have ordered so that they do not cause loss and disappointment to both resellers and online shop owners. The implications of the reseller system in online buying and selling are because online buying and selling with a reseller system is easier to do and does not interfere with other activities, but there is a risk in it if the person doing the buying and selling is not trustworthy.